AM  Vol.10 No.5 , May 2019
On q-Analogues of Laplace Type Integral Transforms of q2-Bessel Functions
ABSTRACT
The present paper deals with the evaluation of the q-Analogues of Laplece transforms of a product of basic analogues of q2-special functions. We apply these transforms to three families of q-Bessel functions. Several special cases have been deducted.

1. Introduction

In the second half of twentieth century, there was a significant increase of activity in the area of the q-calculus mainly due to its application in mathematics, statistics and physics. In literature, several aspects of q-calculus were given to enlighten the strong inter disciplinary as well as mathematical character of this subject. Specifically, there have been many q-analogues and q-series representations of various kinds of special functions. In the case of q-Bessel function, there are two related q-Bessel functions introduced by Jackson [1] and denoted by Ismail [2] as

J μ ( 1 ) ( z ; q ) = ( z 2 ) μ n = 0 ( z 2 4 ) n ( q , q ) μ + n ( q ; q ) n , | z | < 2 (1)

J μ ( 2 ) ( z ; q ) = ( z 2 ) μ n = 0 q n ( n + μ ) ( z 2 4 ) n ( q , q ) μ + n ( q ; q ) n , z (2)

The third related q-Bessel function J μ ( 3 ) ( z ; q ) was introduced in a full case as [3]

J μ ( 3 ) ( z ; q ) = z μ n = 0 ( 1 ) n q n ( n 1 ) 2 ( q z 2 ) n ( q , q ) μ + n ( q ; q ) n , z (3)

A certain type of Laplace transforms, which is called L2-transform, was introduced by Yürekli and Sadek [4] . Then these transforms were studied in more details by Yürekli [5] , [6] . Purohit and Kalla applied the q-Laplace transforms to a product of basic analogues of the Bessel function [7] .

On the same manner, integral transforms have different q-analogues in the theory of q-calculus. The q-analogue of the Laplace type integral of the first kind is defined by [8] as

q L 2 ( f ( ξ ) ; y ) = 1 1 q 2 0 y 1 ξ E q 2 ( q 2 y 2 ξ 2 ) f ( ξ ) d ξ (4)

and expressed in terms of series representation as

q L 2 ( f ( ξ ) ; y ) = ( q 2 ; q 2 ) [ 2 ] q y 2 i = 0 q 2 i ( q 2 ; q 2 ) i f ( q i y 1 ) . (5)

On the other hand, the q-analogue of the Laplace type integral of the second kind is defined by [8] as

q l 2 ( f ( ξ ) ; y ) = 1 1 q 2 0 ξ e q 2 ( y 2 ξ 2 ) f ( ξ ) d q ξ (6)

whose q-series representation expressed as

q l 2 ( f ( ξ ) ; y ) = 1 [ 2 ] 2 ( y 2 ; q 2 ) i q 2 i f ( q i ) ( y 2 ; q 2 ) i . (7)

In this paper we build upon analysis of [8] . Following [9] , we discuss the q-Laplace type integral transforms (4) and (7) on the q-Bessel functions J μ ( 1 ) ( z ; q ) , J μ ( 2 ) ( z ; q ) and J μ ( 3 ) ( z ; q ) , respectively. In Section 2, we recall some notions and definitions from the q-calculus. In Section 3, we give the main results to evaluate the q-analogue of Laplace transformation of q2-Basel function. In Section 4, we discuss some special cases.

2. Definitions and Preliminaries

In this section, we recall some usual notions and notations used in the q-theory. It is assumed in this paper wherever it appears that 0 < q < 1 . For a complex number a, the q-analogue of a is introduced as [ a ] q = 1 q a 1 q . Also, by fixing a , the q-shifted factorials are defined as

( a ; q ) 0 = 1 ; ( a , q ) n = k = 0 n 1 ( 1 a q k ) , n = 1,2, ; ( a ; q ) = lim n ( a ; q ) n . (8)

This indeed lead to the conclusion

( [ n ] q ) ! = ( q ; q ) n ( 1 q ) n , n and ( a ; q ) x = ( a ; q ) ( a q x ; q ) . (9)

The q-analogue of the exponential function of first and second type are respectively given in [10] by

e q ( x ) = 0 x n ( q ; q ) n = 1 ( x ; q ) , | x | < 1. (10)

and

E q ( x ) = 0 ( 1 ) n q n n 1 2 x n ( q ; q ) n , x . (11)

Indeed it has been shown that

e q ( x ) = 1 ( x ; q ) , | x | < 1 and E q ( x ) = ( x , q ) , x (12)

The finite q-Jackson and improper integrals are respectively defined by [11]

0 x f ( t ) d q t = x ( 1 q ) k = 0 q k f ( x q k ) (13)

and

0 / A f ( t ) d q t = ( 1 q ) k q k A f ( q k A ) . (14)

The q-analogues of the gamma function of first and second type are respectively defined in [9] as

Γ q ( α ) = 0 1 / ( 1 q ) x α 1 E q ( q ( 1 q ) x ) d q x , ( α > 0 ) (15)

and

q Γ ( α ) = K ( A ; α ) 0 / A ( 1 q ) x α 1 e q ( ( 1 q ) x ) d q x (16)

where, α 1 > 0 , where K ( A ; α ) is the function given by

K ( A ; α ) = A α 1 ( q / α ; q ) ( α ; q ) ( q t / α ; q ) ( α q 1 t ; q ) . (17)

Some useful results, for x 0, 1, 2, , we use here are given by

Γ q ( α ) = ( q ; q ) ( 1 q ) α 1 k = 0 q k α ( q ; q ) k = ( q ; q ) ( q α ; q ) ( 1 q ) 1 x , (18)

and

q Γ ( α ) = K ( A ; α ) ( 1 q ) α 1 ( 1 A ; q ) k ( q k A ) ( 1 A ; q ) k . (19)

3. Main Theorems

Theorem 1. Let J 2 μ 1 ( 1 ) ( 2 a 1 t ; q 2 ) , , J 2 μ n ( 1 ) ( 2 a n t ; q 2 ) be a set of first kind of q2-Bessel functions, f ( t ) = t Δ 1 j = 1 n J 2 μ j ( 1 ) ( 2 a j t ; q 2 ) , where Δ , a j and μ j for j = 1 , 2 , , n are constants; then the q-analogue of Lablace transformation q L 2 of f ( t ) is given as:

q L 2 ( f ( t ) ; s ) = A Δ j = 1 n ( a j s ) μ j m j = 0 ( a j s ) m j B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 2 ) (20)

and the q-analogue of Laplace transformation q l 2 of f ( t ) is given as:

q l 2 ( f ( t ) ; s ) = A Δ j = 1 n ( a j s ) μ j m j = 0 ( a j s ) m j B m j ( q 2 ) q 2 Γ ( m j + μ j + Δ + 1 2 ) K ( 1 s 2 ; m j + μ j + Δ + 1 2 ) . (21)

where R e ( s ) > 0 , R e ( Δ ) > 0 and

A Δ = ( 1 q 2 ) Δ / 2 [ 2 ] s Δ + 1 ( q 2 ; q 2 ) , B m j ( q 2 ) = ( q 2 μ j + m j + 2 ; q 2 ) ( 1 q 2 ) m j + μ j 1 2 ( q 2 ; q 2 ) m j

Proof. Now,

q L 2 ( f ( t ) ; s ) = ( q 2 ; q 2 ) [ 2 ] s 2 k = 0 q 2 k f ( q k s 1 ) ( q 2 ; q 2 ) k

since

J 2 μ j ( 1 ) ( 2 a j t ; q 2 ) = ( 2 a j t 2 ) 2 μ j m j = 0 ( ( 2 a j t ) 2 4 ) m j ( q 2 ; q 2 ) 2 μ j + m j ( q 2 ; q 2 ) m j

so

q L a ( f ( t ) ; s ) = ( q 2 ; q 2 ) [ 2 ] s 2 k = 0 q 2 k ( q 2 ; q 2 ) k ( q k s 1 ) Δ 1 j = 1 n ( a j q k s 1 ) 2 μ j m j = 0 ( 1 ) m j ( a j q k s 1 ) m j ( q 2 ; q 2 ) 2 μ j + m j ( q 2 ; q 2 ) m j = ( q 2 ; q 2 ) [ 2 ] s Δ + 1 k = 0 q k ( Δ + 1 ) ( q 2 ; q 2 ) k j = 1 n ( a j q k s ) μ j m j = 0 ( 1 ) m j ( a j q k s ) m j ( q 2 ; q 2 ) 2 μ j + m j ( q 2 ; q 2 ) m j = ( q 2 ; q 2 ) [ 2 ] s Δ + 1 j = 1 n ( a j s ) μ j m j = 0 ( 1 ) m j ( a j s ) m j ( q 2 ; q 2 ) 2 μ j + m j ( q 2 ; q 2 ) m j k = 0 q k ( Δ + 1 + m j + μ j ) ( q 2 ; q 2 ) k (22)

Since

Γ q 2 ( α ) = ( q 2 ; q 2 ) ( 1 q 2 ) α 1 k = 0 q 2 k α ( q 2 ; q 2 ) k

putting α = 1 + Δ + m j + μ j 2 , so (22) becomes:

q L s ( f ( t ) ; s ) = 1 [ 2 ] s Δ + 1 j = 1 n ( a j s ) μ j m j = 0 ( 1 ) m j ( a j s ) m j ( 1 q 2 ) 1 + Δ + m j + μ j 2 ( q 2 ; q 2 ) 2 μ j + m j ( q 2 ; q 2 ) m j .

Γ q 2 ( m j + μ j + Δ + 1 2 ) (23)

Since

( q 2 ; q 2 ) 2 μ j + m j = ( q 2 ; q 2 ) ( q 2 q 2 μ j + m j ; q 2 )

so (23) becomes:

q L 2 ( f ( t ) ; s ) = ( 1 q 2 ) Δ / 2 [ 2 ] s Δ + 1 ( q 2 ; q 2 ) j = 1 n ( a j s ) μ j m j = 0 ( a j s ) ( 1 ) m j ( q 2 μ j + m j + 2 ; q 2 ) ( 1 q 2 ) m j + μ j 1 2 ( q 2 ; q 2 ) m j .

Γ q 2 ( m j + μ j + Δ + 1 2 ) = A Δ j = 1 n ( a j s ) μ j m j = 0 ( a j s ) ( 1 ) m j B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 ) 2

Similarly we have

q l 2 ( f ( t ) ; s ) = 1 [ 2 ] 1 ( s 2 ; q 2 ) k = 0 q 2 k ( s 2 ; q 2 ) k ( q k ) Δ 1 j = 1 n J 2 μ j ( 1 ) ( 2 a j q k ; q 2 ) = 1 [ 2 ] 1 ( s 2 ; q 2 ) k = 0 q 2 k ( s 2 ; q 2 ) k ( q k ) Δ 1 j = 1 n ( a j q k ) μ j .

m j = 0 ( a j q k ) m j ( q 2 ; q 2 ) m j + 2 μ j = j = 1 n ( a j ) μ j [ 2 ] m j = 0 ( a j ) m j ( q 2 ; q 2 ) m j + 2 μ j ( q 2 ; q 2 ) m j k = 0 ( s 2 ; q 2 ) k q k ( m j + μ j + Δ + 1 ) ( s 2 ; q 2 )

Now using

q 2 Γ ( α ) = K ( A ; α ) ( 1 q 2 ) α 1 ( 1 A ; q 2 ) k Z ( q K A ) α ( 1 A ; q 2 ) K

with A = 1 s 2 , α = m j + μ j + Δ + 1 2 we get

q l 2 ( f ( t ) ; s ) = j = 1 m ( a j ) μ j [ 2 ] s μ j + Δ + 1 m j = 0 ( a j s ) m j ( 1 q 2 ) m j + μ j + Δ + 1 2 q 2 Γ ( m j + μ j + Δ + 1 2 ) K ( 1 s 2 ; m j + μ j + Δ + 1 2 ) ( q 2 ; q 2 ) m j + 2 μ j ( q 2 ; q 2 ) m j = ( 1 q 2 ) Δ 2 [ 2 ] s Δ + 1 ( q 2 ; q 2 ) j = 1 m ( a j s ) μ j m j = 0 ( a j s ) m j ( 1 q 2 ) m j + μ j 1 2 ( q m j + 2 μ j + 2 ; q 2 ) K ( 1 s 2 , m j + μ j + Δ + 1 2 ) ( q 2 ; q 2 ) m j .

q 2 Γ ( m j + μ j + Δ + 1 2 ) = A Δ j = 1 m ( a j s ) μ j m j = 0 ( a j s ) m j K ( 1 s 2 ; m j + μ j + Δ + 1 2 ) B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 )

Theorem 2. Let J 2 μ 1 ( 2 ) ( 2 a , t ; q 2 ) , , J 2 μ n ( 2 ) ( 2 a t ; q 2 ) be a set of second order q2-Bessel function, f ( t ) = t Δ 1 j = 1 n J 2 μ j ( 2 ) ( 2 a j t ; q 2 ) where Δ , a j and μ j for j = 1 , 2 , , n are constants then q L 2 -transform of f ( t ) is given as:

q L 2 ( f ( t ) , s ) = A Δ j = 1 n ( a j s ) μ j m j = 0 ( 1 ) m j q 2 m j ( m j + 2 μ j ) ( a j s ) m j + μ j B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 ) (24)

and the q-analogue of Laplace transformation q l 2 of f ( t ) is given as:

q l 2 ( f ( t ) ; s ) = A Δ j = 1 n ( a j s ) μ j m j = 0 ( a j s ) m j q 2 m j ( m j + 2 μ j ) K ( 1 s 2 ; m j + μ j + Δ + 1 2 ) B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 2 ) (25)

Proof. Now,

J 2 μ j ( 2 ) ( 2 a j t ; q 2 ) = ( 2 a j t 2 ) 2 μ j m j ( ( 2 a j t ) 2 4 ) m j q 2 m j ( m j + 2 a j ) ( q 2 ; q 2 ) 2 μ j + m j ( q 2 ; q 2 ) m j

so

q L 2 ( f ( t ) ; s ) = ( q 2 ; q 2 ) [ 2 ] s 2 k = 0 q 2 k ( q 2 ; q 2 ) k ( q k s 1 ) Δ 1 j = 1 n ( 2 a j q k s 1 2 ) 2 μ j m j = 0 ( ( 2 a j q k s 1 ) 2 4 ) m j q 2 m j ( m j + 2 μ j ) ( q 2 ; q 2 ) 2 μ j + m j ( q 2 ; q 2 ) m j (26)

By the same argument we can write (26) as

q L 2 ( f ( t ) ; s ) = ( q 2 ; q 2 ) [ 2 ] s Δ + 1 ( q 2 ; q 2 ) j = 1 n m j = 0 ( 1 ) m j q 2 m j ( m j + 2 μ j ) ( q 2 ; q 2 ) m j ( a j s ) m j + μ j ( q 2 μ j + m j + 2 ; q 2 ) k = 0 q k ( m j + μ j + 1 + Δ ) ( q 2 ; q 2 ) k

put α = m j + μ j + Δ + 1 2 in Γ q 2 ( α ) , then

So (25) becomes:

q L 2 ( f ( t ) ; s ) = A Δ j = 1 n ( a j s ) μ j m j = 0 ( 1 ) m j q 2 m j ( m j + 2 μ j ) ( a j s ) m j + μ j B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 )

Similarly

q l 2 ( f ( t ) ; s ) = 1 [ 2 ] 1 ( s 2 ; q 2 ) k = 0 q 2 k ( s 2 ; q 2 ) k ( q k ) Δ 1 j = 1 n ( a j q k ) μ j m j = 0 ( a j q k ) m j q 2 m j ( m j + 2 μ j ) ( q 2 ; q 2 ) m j + 2 μ j ( q 2 ; q 2 ) m j

Put A = 1 s 2 , α = m j + μ j + Δ + 1 2 we get

q l 2 ( f ( t ) ; s ) = 1 [ 2 ] j = 1 n ( a j ) μ j m j = 0 ( a j ) m j q 2 m j ( m j + 2 μ j ) ( 1 q 2 ) m j + μ j + Δ + 1 2 q 2 Γ ( m j + μ j + Δ + 1 2 ) ( q 2 ; q 2 ) m j + 2 μ j K ( 1 s 2 ; m j + μ j + Δ + 1 2 ) s m j + μ j + Δ + 1 = A Δ m j = 0 ( a j s ) m j q 2 m j ( m j + 2 μ j ) K ( 1 s 2 ; m j + μ j + Δ + 1 2 ) B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 2 )

Theorem 3. Let J 2 μ j ( 3 ) ( q 1 a 1 t ; q 2 ) , , J 2 μ n ( 3 ) ( q 1 a n t ; q 2 ) be s set of q2-Bessel functions, f ( t ) = t Δ 1 j = 1 n J 2 μ j ( 3 ) ( q 1 a j t ; q 2 ) where Δ , a j and μ j for j = 1 , 2 , , n are constants. Then we have

q L 2 ( f ( t ) ; s ) = A Δ j = 1 n ( a j q s ) μ j m j = 0 ( 1 ) m j q m j ( m j 1 ) ( a j q s ) m j B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 2 ) (27)

and the q-analogue of Laplace transformation q l 2 of f ( t ) is given by:

q l 2 ( f ( t ) ; s ) = A Δ j = 1 n ( a j q s ) μ j m j = 0 ( a j q s ) m j q m j ( m j 1 ) K ( 1 s 2 ; m j + μ j + Δ + 1 2 ) B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 ) 2 (28)

Proof. Now

J 2 μ j ( 3 ) ( a j q k 1 s 1 ; q 2 ) = ( a j q k 1 s 1 ) 2 μ j m j = 0 ( 1 ) m j q 2 m j ( m j 1 ) 2 ( q 2 a j q k 1 s 1 ) m j ( q 2 ; q 2 ) m j + 2 μ j ( q 2 ; q 2 ) m j

q L 2 ( f ( t ) ; s ) = ( q 2 ; q 2 ) [ 2 ] s 2 k = 0 q 2 k ( q k s 1 ) Δ 1 ( q 2 ; q 2 ) k j = 1 n ( a j q k 1 s 1 ) μ j m j = 0 ( 1 ) m j q m j ( m j 1 ) ( q 2 a j q k 1 s 1 ) m j ( q 2 ; q 2 ) m j + 2 μ j ( q 2 ; q 2 ) m j

put α = m j + μ j + Δ + 1 2 , we get

q L 2 ( f ( t ) ; s ) = A Δ j = 1 n ( a j q s ) μ j m j = 0 ( 1 ) m j q m j ( m j 1 ) ( a j q s ) m j B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 2 )

Similarly

q l 2 ( f ( t ) ; s ) = 1 [ 2 ] 1 ( s 2 ; q 2 ) j = 1 n ( q k 1 ) μ j ( a j ) μ j m j = 0 ( 1 ) m j q m j ( m j 1 ) ( q k m j ) ( q a j ) m j ( q 2 ; q 2 ) m j + μ 2 ( q 2 ; q 2 ) m j k = 0 q k ( Δ + 1 ) ( s 2 ; q 2 ) k .

Put α = m j + μ j + Δ + 1 2 , A = 1 s 2 we get

q l 2 ( f ( t ) ; s ) = ( 1 q 2 ) Δ 2 [ 2 ] s Δ + 1 ( q 2 ; q 2 ) j = 1 n ( a j q s ) μ j m j = 0 ( a j q s ) m j q m j ( m j 1 ) B m j ( q 2 ) Γ q 2 ( m j + μ j + Δ + 1 2 ) K ( 1 s 2 ; m j + μ j + Δ + 1 2 ) .

4. Special Cases

1) Let n = 1 , μ 1 = μ , a 1 = a in above theorems, respectively we have:

q L 2 ( t Δ 1 J 2 μ ( 1 ) ( 2 a t ; q 2 ) ; s ) = A Δ ( a s ) μ m = 0 ( a s ) m B m ( q 2 ) Γ q 2 ( m + μ + Δ + 1 2 ) (29)

q l 2 ( t Δ 1 J 2 μ ( 1 ) ( 2 a t ; q 2 ) ; s ) = A Δ ( a s ) μ m = 0 ( a s ) m K ( 1 s 2 ; m + μ + Δ + 1 2 ) B m ( q 2 ) Γ q 2 ( m + μ + Δ + 1 2 ) (30)

q L 2 ( t Δ 1 J 2 μ ( 2 ) ( 2 a t ; q 2 ) ; s ) = A Δ ( a s ) μ m = 0 ( 1 ) m q 2 m ( m + 2 μ ) B m ( q 2 ) Γ q 2 ( m + μ + Δ + 1 2 ) (31)

q l 2 ( t Δ 1 J 2 μ ( 2 ) ( 2 a t ; q 2 ) ; s ) = A Δ ( a s ) μ m = 0 ( a s ) m q 2 m ( m + 2 μ ) K ( 1 s 2 ; m + μ + Δ + 1 2 ) B m ( q 2 ) Γ q 2 ( m + μ + Δ + 1 2 ) (32)

q L 2 ( t Δ 1 J 2 μ ( 3 ) ( 2 a q 1 t ; q 2 ) ; s ) = A Δ ( a q s ) μ m = 0 ( 1 ) m q m ( m 1 ) ( a q s ) m B m ( q 2 ) Γ q 2 ( m + μ + Δ + 1 2 ) (33)

q l 2 ( t Δ 1 J 2 μ ( 3 ) ( 2 a q 1 t ; q 2 ) ; s ) = A Δ ( a s ) μ m = 0 ( a q s ) m q m ( m 1 ) K ( 1 s 2 ; m + μ + Δ + 1 2 ) B m ( q 2 ) Γ q 2 ( m + μ + Δ + 1 2 ) (34)

2) Put Δ 1 = μ in part (29) above, then

q L 2 ( t μ J 2 μ ( 1 ) ( 2 a t ; q 2 ) ; s ) = ( 1 q 2 ) μ + 1 2 [ 2 ] s μ + 2 ( q 2 ; q 2 ) ( a s ) μ

m = 0 ( a s ) m ( q 2 μ + m + 2 ; q 2 ) ( 1 q 2 ) m + μ 1 2 ( q 2 ; q 2 ) m Γ q 2 ( m + 2 μ + 2 2 ) = ( a s ) μ [ 2 ] s μ + 2 m = 0 ( a s ) m ( q 2 ; q 2 ) m = ( a ) μ [ 2 ] s 2 μ + 2 e q 2 ( a s ) .

3) Put μ = 0 we get

q L 2 ( J 0 ( 1 ) ( 2 a t ; q 2 ) ; s ) = 1 [ 2 ] s 2 e q 2 ( a s ) .

which is the same result cited by [7] .

4) Put Δ 1 in (33), then

q L 2 ( t μ J 2 μ ( 3 ) ( 2 q 1 a t ) ; s ) = ( 1 q 2 ) μ + 1 2 [ 2 ] s μ + 2 ( q 2 ; q 2 ) ( a q s ) μ .

m = 0 ( 1 ) m q m ( m 1 ) ( a q s ) m ( q 2 μ + m + 2 ; q 2 ) ( 1 q 2 ) m + μ 1 2 Γ q 2 ( m + 2 μ + 2 2 ) ( q 2 ; q 2 ) m = ( a q ) μ [ 2 ] s 2 μ + 2 m = 0 ( 1 ) m ( a q s ) m q 2 m m 1 2 ( q 2 ; q 2 ) m = ( a q ) μ [ 2 ] s 2 μ + 2 E q 2 ( a q s ) .

5) Let μ = 0 and a = 0 in (34), then

q L 2 ( t Δ 1 ; s ) = ( 1 q 2 ) Δ 2 [ 2 ] s Δ + 1 1 K ( 1 s 2 ; Δ + 1 2 ) ( 1 q 2 ) 1 2 Γ q 2 ( Δ + 1 2 )

replacing Δ 1 by α , we get

q L 2 ( t α ; s ) = ( 1 q 2 ) α 2 [ 2 ] s α + 2 1 K ( 1 s 2 ; 1 + α 2 ) Γ q 2 ( 1 + α 2 )

which is the same result in [8] .

Acknowledgements

The authors are thankful to Professor S. K. Al-Omari for his suggestions in this paper.

Cite this paper
Alshibani, A. and Alkhairy, R. (2019) On q-Analogues of Laplace Type Integral Transforms of q2-Bessel Functions. Applied Mathematics, 10, 301-311. doi: 10.4236/am.2019.105021.
References
[1]   Jackson, F.H. (1905) The Application of Basic Numbers to Bessel’s and Legendre’s Functions. Proceedings of the London Mathematical Society, 2, 192-220.
https://doi.org/10.1112/plms/s2-2.1.192

[2]   Ismail, M.E.H. (1982) The Zeros of Basic Bessel Function, the Functions Jv+ax(x), and Associated Orthogonal Polynomials. Journal of Mathematical Analysis and Applications, 86, 1-19.
https://doi.org/10.1016/0022-247X(82)90248-7

[3]   Exton, H. (1978) A Basic Analogue of the Bessel-Clifford Equation. Jnanabha, 8, 49-56.

[4]   Yürekli, O. and Sadek, I. (1991) A Parseval-Goldstein Type Theorem on the Widder Potential Transform and Its Applications. International Journal of Mathematics and Mathematical Sciences, 14, 517-524.
https://doi.org/10.1155/S0161171291000704

[5]   Yürelki, O. (1999) Theorems on L2-Transforms and Its Application. Complex Variables, Theory and Application: An International Journal, 38, 95-107.
https://doi.org/10.1080/17476939908815157

[6]   Yürekli, O. (1999) New Identities Involving the Laplace and the L2-Transforms and Their Applications. Applied Mathematics and Computation, 99, 141-151.
https://doi.org/10.1016/S0096-3003(98)00002-2

[7]   Purohit, S.D. and Kalla, S.L. (2007) On q-Laplace Transforms of the q-Bessel Functions. Fractional Calculus and Applied Analysis, 10, 189-196.

[8]   Uçar, F. and Albayrak, D. (2011) On q-Laplace Type Integral Operators and Their Applications. Journal of Difference Equations and Applications, 18, 1001-1014.

[9]   Al-Omari, S.K.Q. (2017) On q-Analogues of the Natural Transform of Certain q-Bessel Function and Some Application. Filomat, 31, 2587-2598.
https://doi.org/10.2298/FIL1709587A

[10]   Hahn, W. (1949) Beitrage Zur Theorie der Heineschen Reihen, Die 24 Integrale der hypergeometrischen q-Differenzengleichung, Das q-Analogon der Laplace Transformation. Mathematische Na-chrichten, 2, 340-379.
https://doi.org/10.1002/mana.19490020604

[11]   Kac, V.G. and De Sele, A. (2005) On Integral Representations of q-Gamma and q-Beta Functions. Accademia Nazionale dei Lincei, 16, 11-29.

 
 
Top